A Mathematical Model for Predicting the Impact of Dust Storms on the Performance of PV Solar Systems. - Sami M Sharif (University of Khartoum Engineering Journal, 2025)
This study presents a mathematical model to predict the impact of dust storms on solar irradiance and photovoltaic (PV) system performance, with a focus on arid regions like Sudan. Using lidar data and locally collected dust samples, the model analyzes the relationship between dust particle size distribution, extinction coefficients, and visibility. Results indicate that dust storms significantly increase optical depth and light attenuation, particularly at low sun elevation angles, leading to substantial reductions in solar irradiance. The proposed model incorporates optical and meteorological parameters—such as normalized polarizability, visibility, and particle density—within a semi-analytical framework. Unlike traditional empirical models, it integrates region-specific dust properties and physical particle behavior, enhancing predictive accuracy for PV output losses. The model predicts irradiance losses of up to 50% during severe dust events, aligning well with reported field observations from similar environments in the Middle East and North Africa. This work contributes a valuable tool for solar energy forecasting and system planning in dusty regions. It also offers insights into visibility degradation during dust storms, supporting applications in both energy and environmental monitoring.